2010
DOI: 10.1016/j.pep.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of bioactive soluble human leukemia inhibitory factor from recombinant Escherichia coli using thioredoxin as fusion partner

Abstract: CitationPreparation of bioactive soluble human leukemia inhibitory factor from recombinant Escherichia coli using thioredoxin as fusion partner. This is a pre-or post-print of an article published in Tomala, M., Lavrentieva, A., Moretti, P., Rinas, U., Kasper, C., Stahl, F., Schambach, A., Warlich, E., Martin, U., Cantz, T., Scheper, T. Preparation of bioactive soluble human leukemia inhibitory factor from recombinant Escherichia coli using thioredoxin as fusion partner regard to large scale cultures of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…The hLIF fusion proteins purities were greater than 95% (Table 1). The yields of His 6 -hLIF and Trx-His 6 -hLIF fusion proteins in this work were higher than previously reported (Gearing et al, 1989;Samal et al, 1995;Tomala et al, 2010).…”
Section: Expression and Purification Of Recombinant Hlif Fusion Proteinscontrasting
confidence: 65%
See 2 more Smart Citations
“…The hLIF fusion proteins purities were greater than 95% (Table 1). The yields of His 6 -hLIF and Trx-His 6 -hLIF fusion proteins in this work were higher than previously reported (Gearing et al, 1989;Samal et al, 1995;Tomala et al, 2010).…”
Section: Expression and Purification Of Recombinant Hlif Fusion Proteinscontrasting
confidence: 65%
“…Many studies have successfully used Escherichia coli to produce several human growth factors and cytokines, such as interleukin-1 (Furutani et al, 1985), interleukin-4 (van Kimmenade et al, 1988), epidermal growth factor (Shimizu et al, 1991;Abdull Razis et al, 2008), fibroblast growth factor (Squires et al, 1988;Gasparian et al, 2009) and LIF (Gearing et al, 1989;Samal et al, 1995;Tomala et al, 2010) for therapeutic and clinical purposes. Although, recombinant human LIF (hLIF) is available and has been successfully produced in E. coli expression systems, they still require many steps of downstream processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells play a primary role in cell therapies and tissue replacement therapies [6,7]. Recently, rhLIF was successfully produced and purified by several groups using different kinds of expression systems such as E. coli [8][9][10], yeast cells and even in rice [11]. An issue arising from this process is the soaring cost of LIF and other cytokines in pluripotent stem cells research.…”
Section: Introductionmentioning
confidence: 99%
“…An issue arising from this process is the soaring cost of LIF and other cytokines in pluripotent stem cells research. Numerous studies have suggested that the cost of commercially produced LIF accounts for about 90 % pluripotent stem cells culture medium [8]. It is urgent to obtain various forms of LIF in high quantities and at a low cost and biological active.…”
Section: Introductionmentioning
confidence: 99%